PENGARUH NILAI-NILAI GURINDAM DUA BELAS UNTUK MENINGKATKAN HUBUNGAN SOSIAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 25 PEKANBARU - Hidayani, Saniah; Saam, Zulfan; Mardes, Siska (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the differences in social relations before and after the applied Gurindam Dua Belas values through group guidance and to know the influence of the Twelve Gurindam Values through group guidance to improve students' social relations. The research was conducted in Pekanbaru State Middle School of 8 subjects with purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used was a social relations questionnaire. The results showed that there were differences in social relations before and after the Gurindam Dua Belas values were given with a significance value of 0.012 <0.05. In addition, based on the Spearman rank test it is known that there is a significant influence between the Twelve Gurindam Values on the social relations of students with a significance value of 0.003 <0.05. The influence of the Twelve Gurindam Values on students' social relations is 79.5% while 20.5% is influenced by other factors that originate from within and from the student's environment. From the results obtained, it is recommended that all people should continue to preserve cultural values in the Gurindam Dua Belas, whose content is able to increase character values, social values, and moral values to encourage the development of social relations related to cooperation, accommodation and assimilation.Key Words : Gurindam dua belas Values, Social Relations, Group Guidance